Modelling and Production of artillery firing-tables: case-study. (March 2020) - Mady, Mohamed; Khalil, Mostafa; Yehia, Mahmoud
Abstract: Projectile firing accuracy is an important artillery issue to increase killing probability with minimum number of rounds per target. This can be achieved through constructing a firing-table (FT) with both standard and non-standard conditions. Therefore, lot of rounds need to be shoot for different target ranges as well as meteorological conditions to increase such firing accuracy. Developing an accurate computational FT prior to shoots has the advantages of minimizing the cost and providing preliminary prediction of dispersion. In this study, a computational FT algorithm has been proposed based on the modified-point-mass projectile trajectory model for solving the ballistics problem. A flow-chart is proposed to illustrate the FT production levels and the corresponding procedures. A case study for 155mm-M107-HE projectile is utilized. In order to validate the proposed algorithm, a comparison has been implemented with results obtained from the well-known commercial package PRODAS. Finally, based on real firing data available including the corresponding meteorological conditions, a provisional firing table has been developed.